How do spinopelvic characteristics change post-total hip arthroplasty?: A longitudinal assessment raising awareness of the postoperative period - Pour, Aidin E.; Innmann, Moritz Maximilian; Reichel, Franz; Schaper, Bibiane; Renkawitz, Tobias; Merle, Christian; Grammatopoulos, George (The journal of arthroplasty, 2024)
Background - Spinopelvic characteristics, including sacral slope (SS), are commonly evaluated in different positions pre-total hip arthroplasty (THA). This study aimed to: 1) investigate the change in spinopelvic parameters at 7 days (early) and 1-year post-THA; and 2) identify patient characteristics associated with a change in SS of more than 7° post-THA. - Methods - We prospectively studied 250 patients who underwent unilateral THA [132 women, age 66 years (range, 32 to 88)] and underwent biplanar images preoperatively and at 7 days and 1-year post-THA. Parameters measured included pelvic incidence, standing lumbar lordosis, SS, and proximal femoral angle (PFA). A SS change ≥ 7° was considered the threshold as it would result in more than a 5° change in cup orientation. - Results - Early post-THA SSstanding remained within ± 6º from preoperative measurements in 75% of patients, reduced by ≥ 7° in 9%, and increased by ≥ 7° in 16%. Those that showed a reduction in SS had the lowest PFA and the highest SS pre-THA (P = .028, .107, and < 0.001, respectively). From 7 days until the 1-year mark, pelvic tilt increased, SS reduced (mean: -4º, range: −29 to 17º, P < .001), and patients stood with greater hip extension ΔPFAstanding (mean 7°, range: −34 to 37°, P < .001). At 1 year, SSseated had remained within ± 6º, relative to the pre-THA value, in 49% of patients. - Conclusions - Standing spinopelvic characteristics, especially SSstanding, remain within ±6° in three-quarters of patients both early- and at 1-year post-THA. In the remaining cases, pelvic tilt changes significantly. In 9% of cases, SS reduces ≥ 7° early THA, probably due to the alleviation of fixed-flexion contractures. The SSseated changes by ≥ ± 7° in almost 50% of cases in this study, and its clinical value as a preoperative planning tool should be questioned. - Level of Evidence - Level II, diagnostic study.
Gesehen am 27.02.2025
Online verfügbar: 8. März 2024, Artikelversion: 3. September 2024